ANALISIS PERHITUNGAN KOMISI AGENT ASURANSI PADA PT.GENERALI LIFE INSURANCE CABANG MEDAN - Sutrisno, Pratama (Universitas Medan Area, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â A commission calcuation is very important for the company to know the performance of the agent. In addition, the calculation of the commission aims to know the commission of insurance agents on PT.GENERALI Life Insurance. In the calculation of the companyâs commission using the method based on working time so that obtained more accurate, fast, precise in reducing the risk of calculating the commission. The type of data used in this study are primary and secondary data, and data sources used in the form of internal and external. Dat collection methods used are field research and library research. Method of data analysis used quantitative descriptive method. Seen from the results of research used by the author, the conclusion that PT.GENERALI Life Insurance has a commission calculation taht is very appropriate with the agent. However, the lack of detailed calculation of commisions makes the agent feel less satisfied. After analyzed the commission calculation has additional reward again so that agent/marketer can motivate himself to achieve the target company.Â Keywords : Insurance Agent Commission